2017
DOI: 10.12965/jer.1734942.471
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cardiopulmonary responses and isokinetic moments: the optimal angular velocity for muscular endurance

Abstract: Most protocols for testing and rehabilitation for recovery and improvement of muscular endurance have been set at 180°/sec, 240°/sec, and 300°/sec. These protocols can cause confusion to clinical providers or other researchers. This study was aimed at investigating the optimal isokinetic angular speed for measuring or developing muscular endurance after assessing the relationship between cardiopulmonary responses and isokinetic moments. This study was conducted with 31 male and female college students. Graded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In this context, the results of the total work corrected for body mass were significantly lower in deaf players, suggesting that lower values of total work may result in reduced cardiorespiratory fitness, measured by an incremental exercise test. Recently, the association between aerobic performance and total work was observed by other researchers (Lee et al, 2017). Furthermore, a significant relationship between functional tests and isokinetic muscle strength was found in soccer players and futsal players (de Lira et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In this context, the results of the total work corrected for body mass were significantly lower in deaf players, suggesting that lower values of total work may result in reduced cardiorespiratory fitness, measured by an incremental exercise test. Recently, the association between aerobic performance and total work was observed by other researchers (Lee et al, 2017). Furthermore, a significant relationship between functional tests and isokinetic muscle strength was found in soccer players and futsal players (de Lira et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
“…Our study found that higher absolute PT values of knee flexors and extensors are associated with higher VO 2max values. Moreover, we found a correlation with the total work of the knee extensors, which is the energy used for muscular effort during movement, i.e., the product of torque by angular displacement (Lee et al, 2017). In this context, the results of the total work corrected for body mass were significantly lower in deaf players, suggesting that lower values of total work may result in reduced cardiorespiratory fitness, measured by an incremental exercise test.…”
Section: Discussionmentioning
confidence: 92%
“…The axes reported in Table 2 and Table 3 represent the following: (1) the X-axis represents vertical displacement, which is the distance between the highest and lowest positions of the volunteer’s hand during bicep extension and flexion; (2) the Y-axis represents horizontal displacement, which is the sideways vibration of the volunteer’s hand during bicep extension and flexion; (3) the Z-axis represents depth displacement, which represent the farthest and nearest positions of the volunteer’s hand from their body during bicep extension and flexion. Figure 3 shows the data pattern changes along the horizontal axis, which indicates the changes in completion time, whereas the vertical axis indicates the changes in angular velocity according to muscular endurance [ 45 ]. As time passed by, we observed the loss in muscle endurance and angular velocity during fatigue presence using the gyroscope and the accelerometer.…”
Section: Methods: Data Processing and Experiments Setupmentioning
confidence: 99%
“…We look for data pattern changes along the horizontal axis which indicates the changes in completion time whereas the vertical axis indicates the changes in angular velocity according to muscular endurance [ 36 ]. To analyze the data pattern changes in the horizontal axis, we measured the time required to complete the first set of biceps repetitions for each volunteer, which is the time interval from the 1st repetition until the end of the 15th repetition.…”
Section: Experiments Evaluationmentioning
confidence: 99%
“…Then, we calculate the difference in completion time between each set compared to the first set. To analyze the data pattern changes in the vertical axis, we measured the absolute magnitude of each repetition in the first set to calculate the muscular endurance [ 36 ] during the first set of biceps repetitions. We repeated the same approach to measure the muscular endurance for the remaining sets separately.…”
Section: Experiments Evaluationmentioning
confidence: 99%